Bilateral renal vein thrombosis in a preterm with Netherton syndrome - Roche-Gomez, Ana; Voskanyan, Diana; Śladowska-Kozłowska, Joanna; Bassanese, Giulia; Schmitt, Claus P. (Pediatric nephrology, 2025)
Netherton syndrome (NS) is a rare autosomal recessive syndrome caused by mutations in the serine protease inhibitor of the Kazal type 5 (SPINK5) gene. Patients are characterized by the classic triad of congenital ichthyosiform erythroderma, a hair shaft abnormality termed trichorrhexis invaginata and atopic diathesis. These children require meticulous fluid and salt control from the first day of life to prevent kidney damage due to the defective skin barrier.